2021
DOI: 10.1049/mna2.12093
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot preparation of small lipid‐indocyanine green nanoparticles to induced intracellular oxidative/thermal stress damage for effective colorectal cancer therapy

Abstract: In the current study, a one-pot method to prepare small lipid-indocyanine green (ICG) nanoparticles (L-ICG NPs) is proposed for the treatment of colorectal cancer. The L-ICG NPs showed size distribution at around 20 nm with high stability and biocompatibility. In addition, they can respond to light irradiations to exert oxidative/thermal stress damage, which showed effective anticancer benefits in vitro and in vivo using HT-29 cells as the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A study reported by Bi [7] described a one-pot approach to manufacture tiny lipid-indocyanine green (ICG) nanoparticles (L-ICG NPs) for colorectal cancer therapy. L-ICG NPs were stable, biocompatible, and 20 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported by Bi [7] described a one-pot approach to manufacture tiny lipid-indocyanine green (ICG) nanoparticles (L-ICG NPs) for colorectal cancer therapy. L-ICG NPs were stable, biocompatible, and 20 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells selectively apoptozed due to PL-induced oxidative stress. A study reported by Bi [ 7 ] described a one-pot approach to manufactuing small nanoparticles of lipid-indocyanine green (ICG), (with the abbreviated form of “L-ICG NPs”) for the treatment of colorectal neoplasms. In the scientific context of a NIR-mediated cancer treatment that has been limited by photothermal drugs’ low NIR absorption and photosensitive molecules’ poor loading efficiency, Choi [ 8 ] created rGO, a nanocomposite under the form of a mesoporous silica-coated reduced graphene oxide that could encapsulate indocyanine green (ICG) and increase PTT/PDT efficiency in vivo and in vitro.…”
Section: Methodsmentioning
confidence: 99%